Essays on the growth and investment of small German firms - Habermann, Harald (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2017)
In 2013, the European Commission adopted the so called "Entrepreneurship 2020 Action Plan" to ease the creation of new ventures and to support the takeover of existing firms. The goal is to create a supportive environment for entrepreneurs to thrive and grow (European Commission 2013). This shows that the European Union puts its efforts to support small firms as they are seen as means for Europe's sustainable economic growth. However, the successful processes of growth and investment are complex and depend on different determinants. The present thesis focuses on the firm level and analyzes in three independent articles: how small firms invest over time, how new ventures grow and which variables influence growth, how small firms grow after business takeover and which variables influence growth. The framework that connects these articles forms the content-related focus on the early stage of development of small firms and the methodological and analytical approaches that comply with up-to-date and adequate statistical analysis techniques. Supported by an extensive dataset, which is the foundation of all three articles, it is possible to investigate empirically different open research questions using bivariate and multivariate analysis techniques. Thus, this thesis also serves the research needs for more multivariate analyses for small firms, for which so far mainly cross-sectional studies have been conducted.
Aufsätze über Wachstum und Investitionen kleiner deutscher Firmen
Keywords: Kleinbetrieb; Investition; Wirtschaftswachstum; Entrepreneurship; Unternehmensgründung; 330 Wirtschaft